An elegy for Dr Sajia - Dont we need more than a gentle societal push to end violence against women? (Bangladesh Medical Journal, 2014)
DOI: http://dx.doi.org/10.3329/bmj.v42i1.18980 Bangladesh Med J. 2013 Jan; 42 (1): 38